Adsorption of 2-Butanone on Pristine Graphene: A First-Principles Study - Viet Bac, Phung Thi; Trong Lam, Pham; An, Dinh Van (VNU Journal of Science: Mathematics - Physics, 2020)
The adsorption mechanism of 2-butanone (ethyl methyl ketone) on the surface of graphene is investigated by using Density Functionals Theory (DFT). A 2-butanone molecule is chosen as a selected example of main volatile organic compounds (VOCs) in exhaled breath. To describe the absorption of 2-butanone and graphene substrate, we have performed DFT simulations including van de Waals (vdW) interactions implemented in the Vienna Ab-initio Simulation Package (VASP). The global minimum energy configurations and binding energies for a 2-butanone molecule adsorbed on graphene are determined by using Computational DFT-based Nanoscope tool for imaging the binding possibility of the adsorbed molecules on the graphene surface. The adsorption energy profiles are calculated by three functionals of van der Waals interactions: revPBE-vdW, optPBE-vdW, and vdW-DF2. It is shown that the adsorption energy is highly sensitive to the vdW functionals. The fundamental insights of the interactions between 2-butanone and graphene through molecular doping, i.e., charge transfer are discussed in detail.